Quantitative analysis of the supernatant from host and transfected CHO cells using iTRAQ 8‐plex technique. Issue 10 (28th April 2016) - Zhu, Guijie; Sun, Liangliang; Albanetti, Thomas; Linkous, Travis; Larkin, Christopher; Schoner, Ronald; McGivney, James B.; Dovichi, Norman J.
ABSTRACT: We employed UPLC‐MS/MS with iTRAQ 8‐plex labeling to quantitatively analyze the supernatant produced by two Chinese hamster ovary (CHO) cell lines (CHO K1SV and CHO CAT‐S). In each case, the supernatant from the host and three transfected clones were analyzed at days 5, 7, and 10 of culture. A total of eight iTRAQ 8‐plex experiments were performed. For each cell line, the overlap of supernatant protein identifications between transfected clones is over 60%. Over 70% of the supernatant proteins in the CHO K1SV host cell line are present in the CHO CAT‐S cell line. For the CHO K1SV cell line, the overlap in supernatant protein identifications between the host cell line and the transfected clones is >59%. For the CHO CAT‐S cell line, the overlap between supernatant protein identifications for the transfected clone and host cell is >45%. These differences in the supernatant protein identifications between transfected clones in each cell line and between the two host cell lines are not significant. We used cluster analysis to characterize the change in supernatant protein expression as a function of cell culture time. Roughly <60% of the supernatant proteins show significant change across the three time points (ratio >1.3 or <0.7). We also used cluster analysis to compare changes in supernatant protein expression between the host and three transfected clones at each time point. Greater than 65% of the common proteins in the CHO K1SV cell line supernatant and over 54% in the CHO CAT‐S cell line supernatant show no significant expression difference between host and the three transfected clones. Data are available via ProteomeXchange with identifier PXD003462. Biotechnol. Bioeng. 2016;113: 2140–2148. © 2016 Wiley Periodicals, Inc. Abstract : Experimental design for 8‐plex iTRAQ quantitative proteomic analysis of the expression difference of supernatant proteins from transfected clones and untransfected host cells. Experiments employed the CHO K1SV and CHO CAT‐S cell lines. Three clones and the parent cell line were analyzed for both cell lines.